ANALISA REMAINING LIFE DAILY STORAGE TANK DI PLTMG SERAM PEAKER 20 MW MASOHI – MALUKU TENGAH - Nur Aisyah Utami Kelian; Erwin Patikayhattu; Nevada. J. M. Nanulaitta; Meiti Leatemia (Jurusan Teknik Mesin, 2024)
Increased global energy demand has resulted in rapid growth in the oil and gas industry, including in Indonesia. Storage tanks play an important role in the storage of large quantities of liquids and must comply with strict technical standards and government regulations, such as American Petroleum Institute (API) 650, 653, and 575 and Permen of ESDM No. 32 of 2021. Seram Peaker 20 MW Masohi-Maluku Tengah MHP, as a vital asset for providing electrical energy, has a fuel storage tank that has never been inspected since the beginning of its operation. Non-compliance with API 653 standards potentially poses a risk of structural damage, leakage, and disruption to fuel supply. This research identifies the importance of periodic structural integrity evaluation using an Ultrasonic Thickness Gauge GM 100 to measure the decrease in plate thickness due to corrosion and predict the remaining service life of the tank. The results of the calculation show that each course starting from course 1-5 is 109.4 years, 72.3 years, 56.9 years, 43.6 years, 38 years, this shows that the Daily Storage Tank PLTMG Seram Peaker 20 MW Masohi-Central Maluku can operate for the next 38 years. Keywords : Storage Tank, Remaining Life, Inspections, UTG, Corrosion Rate